2023
DOI: 10.1038/s41467-023-36708-5
|View full text |Cite
|
Sign up to set email alerts
|

PHGDH arginine methylation by PRMT1 promotes serine synthesis and represents a therapeutic vulnerability in hepatocellular carcinoma

Abstract: Serine synthesis is crucial for tumor growth and survival, but its regulatory mechanism in cancer remains elusive. Here, using integrative metabolomics and transcriptomics analyses, we show a heterogeneity between metabolite and transcript profiles. Specifically, the level of serine in hepatocellular carcinoma (HCC) tissues is increased, whereas the expression of phosphoglycerate dehydrogenase (PHGDH), the first rate-limiting enzyme in serine biosynthesis pathway, is markedly downregulated. Interestingly, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 72 publications
(131 reference statements)
0
23
0
Order By: Relevance
“…These findings underscore the effectiveness of PRMT1 inhibition as a promising strategy for MM therapy, particularly in relapsed/refractory cases where alternative treatment options are limited. GSK3368715 is a potent oral PRMT type I inhibitor that exhibits strong anti-cancer activity in vivo in many preclinical models (29)(30)(31). This inhibitor was used in the clinical trial for solid tumors and diffused large B-cell lymphoma (NCT03666988).…”
Section: Discussionmentioning
confidence: 99%
“…These findings underscore the effectiveness of PRMT1 inhibition as a promising strategy for MM therapy, particularly in relapsed/refractory cases where alternative treatment options are limited. GSK3368715 is a potent oral PRMT type I inhibitor that exhibits strong anti-cancer activity in vivo in many preclinical models (29)(30)(31). This inhibitor was used in the clinical trial for solid tumors and diffused large B-cell lymphoma (NCT03666988).…”
Section: Discussionmentioning
confidence: 99%
“…Another research group reported that the activation of PHGDH through the monomethylation of different arginine residue R236 (located at the substrate recognition site) by PRMT1 shunts into the glutathione synthetic pathway to reduce ROS levels for hepatocellular carcinoma progression ( 57 ). However, our results indicate a glutathione-independent mechanism to acquire chemoresistance of TNBC ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…PRMT1, the first identified arginine methyltransferase, plays a crucial role in a range of biological processes, including the cell cycle, DNA damage, transcription and signal transduction [6] . Recent studies have demonstrated a regulatory role of PRMT1 in cellular metabolic pathways, including serine metabolism [7] , lipid metabolism [8,9] and glucose homeostasis [10][11][12] . In addition, high PRMT1 expression is known to contribute to cell proliferation in multiple tumors [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%